2015
DOI: 10.1016/j.jcat.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Alkane reforming on partially sulfided CeO2 (1 1 1) surfaces

Abstract: a b s t r a c tCleanup of biomass gasification effluent requires a catalyst that can reform methane and larger hydrocarbons while tolerating the presence of H 2 S or, ideally, that can act as a sulfur sorbent while reforming hydrocarbons. We utilize density functional theory (DFT) methods to examine the impact of oxide sulfidation on the reforming of methane and the initial steps of propane reforming, using M-doped CeO 2 catalysts. On a ceria oxy-sulfide surface, surface oxygen atoms remain active for CAH bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…However, the remaining question is whether such a mechanism can be applied in the present work and whether this strategy can be extended to the activation of other alkane molecules. Furthermore, the reaction mechanism during alkane reforming over sulfated CeO 2 surface was also reported by them, which illustrated that there was a slight preference for CH 3 * species to bind to surface sulfur atoms . More recently, the sulfur-accelerated ceria catalyst was reported for deNO x reaction, and it is revealed that Brønsted acid sites originated from the protons on surface sulfates were created by sulfation treatment .…”
Section: Introductionmentioning
confidence: 65%
“…However, the remaining question is whether such a mechanism can be applied in the present work and whether this strategy can be extended to the activation of other alkane molecules. Furthermore, the reaction mechanism during alkane reforming over sulfated CeO 2 surface was also reported by them, which illustrated that there was a slight preference for CH 3 * species to bind to surface sulfur atoms . More recently, the sulfur-accelerated ceria catalyst was reported for deNO x reaction, and it is revealed that Brønsted acid sites originated from the protons on surface sulfates were created by sulfation treatment .…”
Section: Introductionmentioning
confidence: 65%
“…For Pd/Ce7 the slightly more negative order results suggest some competitive inhibition by water, due possibly to elimination of oxygen vacancies. For La/Ce3 and Re/Ce3/Zr54, the high negative orders signify that the water greatly changed the catalyst structure resulting in the elimination of oxygen vacancies that according to DFT studies constitute the initial active sites. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…For La/Ce3 and Re/Ce3/ Zr54, the high negative orders signify that the water greatly changed the catalyst structure resulting in the elimination of oxygen vacancies that according to DFT studies constitute the initial active sites. 10,11,57 Most researchers have reported some increase in tar reforming activity and lower coke deposition when the partial pressure of water is increased. 22,25,51,58−60 However, there appears to exist an optimum water partial pressure, for most catalysts.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The selective hydrodeoxygenation (HDO) of lipid was performed using sulfur-and non-sulfur-containing metal catalysts due to their relatively high stability in non-polar phases [1,14]. Ni-and Co-based catalysts are used for the HDO of fatty acids and lipids into alkanes at ca.…”
Section: Introductionmentioning
confidence: 99%